Hip Adductor Longus Tendon Origin Anatomy Is Consistent and May Inform Surgical Reattachment - Michael A. Perrone, M.D., M.P.H; Ali Noorzad, M.D; Mathew Hamula, M.D; Melodie Metzger, Ph.D; Michael Banffy, M.D; Michael Gerhardt, M.D (Elsevier, 2021)
Purpose: To define the topographic anatomy of the footprint of the adductor longus origin on the pubis and its underlying bony morphology to better inform surgical repair of adductor longus tendon injuries. Methods: Five cadaveric pelvis specimens were dissected, making 10 adductor footprints available for analysis. The adductor longus tendon origin was isolated and the surrounding tissue debrided. The circumference of the tendinous attachment to the pubic crest was marked before excising the tendon and fibrocartilage enthesis from the pubis. Radiopaque paint was prepared by mixing 30 mL of all-purpose acrylic paint (Anita's no. 11150 Island Blue; Rust-Oleum Corp, Vernon Hills, IL) with 15g of E-Z-HD 98% w/w barium sulfate (Bracco Diagnostics Inc., Anjou Quebec, Canada) and applied to the marked footprint. The specimens underwent a 1.0-mm slice computed tomographic scan with 3-dimensional reconstructions. Synapse PACS (FujiFilm, Valhalla, NY) software for measurements of the tendon footprint and underlying bone. Results: Average age and weight of the specimens at the time of death was 37 years and 204.6 ± 48.7 lbs, respectively. The width and length of the tendon origin was 12.0 ± 1.1 mm and 10.9 ± 1.1 mm, respectively. The distance of the center of the footprint from the center of the pubic tubercle was 8.5 ± 1.4 mm lateral and 12.2 ± 0.4 mm caudal. The osseous thickness underlying the footprint was 18.7 ± 3.7 mm at an angle of 34.5 ± 1.5° in relation to the sagittal plane. The correlation between specimen body weight and the thickness of the bone underlying the footprint was strongly positive (r = 0.92). Conclusions: We found that there is a consistent angle from the center of the adductor longus tendon footprint to the point of maximal underlying bony thickness, as well as a positive correlation between body mass index and osseous thickness, which may inform anatomic reattachment of this tendon. Clinical Relevance: Our findings will assist surgeons in identifying the footprint of the adductor longus tendon and safely perform anatomic repair of adductor longus tendon avulsions.